Advocacy - Boon, Andrew (Essential legal skills, 1993)
Introduces the practice of advocacy, drawing on a wide range of examples from the United Kingdom and other common law jurisdictions. Through the use of exercises, the reader is encouraged to think about effective advocacy. Detailed materials offer civil and criminal advocacy simulations.